The significance of the tactical training of volleyball players of different skill levels in their play activities - B.O. Artemenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : To determine the features of tactical thinking volleyball players of different skill levels and the importance of this function during their competitive activities. Material and methods : the study involved in 28 different sports categories players aged 17-34 years. Used interactive methods «Volleyball-Test». Results: revealed that the level of masters of sports players had values at 64.22 % - tactical thinking in the attack, and 59.46 % - tactical thinking in defense. Accordingly - Candidate Master of Sports (42.24 % and 40.19 %) and players Ι-ΙΙΙ bits (34.44 % and 28.89 %). The dependence of the quality of players in competitive activity level masters of sports of tactical thinking in the attack at r = 0,66, and to protect r = 0,54. As appointed a relationship as competitive activities and tactical thinking of attacking r = 0,58. The player Ι-ΙΙΙ bits of data dependencies as competitive activities of tactical training have been identified. Conclusions : The set features suggest the development of tactical thinking in sports games acquiring playing experience of the players.